Exploring the Influence of Behavioral Biases on Decision-making in Digital Finance: Implications for Financial Inclusion and Consumer Protection - Chuahan, Rahul; Chavda, Kishan (Journal of Economics, Assets, and Evaluation, 2024)
This research paper investigates the influence of socioeconomic factors on financial behaviors among millennials. Through an analysis of variance (ANOVA) approach, the study examines the significance of socioeconomic variables on various aspects of financial decision-making, including online banking usage, saving priorities, comfort with investment decisions, and reliance on digital financial resources. The findings reveal minimal to modest effects of socioeconomic factors on these financial behaviors among millennials. While some variables such as familiarity with digital financial resources show slightly higher effect sizes, overall, socioeconomic factors explain only a small proportion of the variance in financial behaviors. These results suggest that other factors beyond socioeconomic status may also play significant roles in shaping financial decision-making among millennials. The study contributes to the existing literature by highlighting the nuanced relationship between socioeconomic factors and financial behaviors among millennials. It underscores the importance of considering multiple determinants when analyzing financial decision-making processes. Future research could explore additional factors such as personality traits, cultural influences, and technological advancements to provide a more comprehensive understanding of millennial financial behaviors. Moreover, longitudinal studies could offer insights into the dynamic nature of financial decision-making and its evolution over time. Understanding these factors is crucial for policymakers, financial institutions, and educators to develop targeted interventions and strategies aimed at promoting financial well-being among millennials in an increasingly complex financial landscape.